ISOLATION, CHARACTERIZATION AND IDENTIFICATION OF DIESEL ENGINE OIL DEGRADING BACTERIA FROM GARAGE SOIL AND THEIR BIOREMEDIATION POTENTIAL - SHWETHA SREEKUMAR; LAKSHMI GIRIJA; ANSHA RAVEENDRAN; ROOPA PRASAD (International Journal of Pharma and Bio Sciences, 2016)
Diesel engine oil, which is one of the major products of crude oil, constitutes a major source of pollution to our environment. Bioremediation of hydrocarbon-contaminated soils, which exploits the ability of microorganisms to degrade and/or detoxify organic contamination, has been established as an efficient, economic, versatile and environmentally sound treatment. In this paper we report the isolation and screening of diesel oil degrading microorganisms from garage soil and the rates of biodegradation of diesel engine oil by microorganisms were studied. One of the potent microorganisms was identified as Gordonia terrae strain. The tolerance level of three microorganisms to diesel engine oil was also determined using gravimetric method. Percentage degradation of diesel oil by three different microorganisms and consortium was studied.